2013
DOI: 10.1590/s1415-790x2013000100014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à desnutrição e ao excesso de peso em menores de cinco anos nos seis maiores municípios do Maranhão

Abstract: Prevalences of malnutrition and overweight among children under five years and its association with socioeconomic, demographic and health indicators were estimated for the six largest municipalities of Maranhão, in 2006/2007. By means of a household survey, a sample of 1214 children under five years of age was randomly selected. Two-stage cluster sampling was used, representing the six municipalities of Maranhão with over one hundred thousand inhabitants. Standardized questionnaire was administered to mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
2
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
(16 reference statements)
3
4
2
15
Order By: Relevance
“…However, prevalence in current study is consistent with other studies at different locations in Brazil (Chagas et al, 2013;Saavedra & Câmara, 2010;Silva & Moura, 2010;Silveira et al, 2010;Souza, Benício, Castro, Muniz, & Cardoso, 2012). The above indicated that there may be populations where acute malnutrition is significant from the point of view of public health.…”
Section: Discussionsupporting
confidence: 91%
“…However, prevalence in current study is consistent with other studies at different locations in Brazil (Chagas et al, 2013;Saavedra & Câmara, 2010;Silva & Moura, 2010;Silveira et al, 2010;Souza, Benício, Castro, Muniz, & Cardoso, 2012). The above indicated that there may be populations where acute malnutrition is significant from the point of view of public health.…”
Section: Discussionsupporting
confidence: 91%
“…Deficit = > -2 SD; Eutrophy = -1 > SD > +1; Excess = < + 2 SD between 1 and 11 years of age of the city of La Plata, Argentina. The study entitled "Health Care in Maranhão" ("Atenção à Saúde no Maranhão") 33 , undertaken in 2006/7 on children of less than 5 years of age, found prevalences of undernourishment by the indices weight/age (4.5%) and weight/height (3.9%) greater than those observed in this present study. It also found a prevalence of 6.7% of overweight for height, below those observed for the municipalities of Barra de São Miguel and Cabedelo, and greater than that observed in the municipality of Tibau do Sul.…”
Section: Resultscontrasting
confidence: 83%
“…Chagas et al 33 found a prevalence of low height for age greater than those observed in this study, with a percentage of 8.5% of children of less than five years of age residing in municipalities of Maranhão with a height for age deficit.…”
Section: Discussioncontrasting
confidence: 66%
“…A proporção de crianças usuárias de creches do presente estudo com excesso de peso/estatura (8,36%) foi superior à reportada na PNDS 10 para as crianças brasileiras menores de 5 anos (7,3%), bem como em relação à região Nordeste (7,1%). Nota-se ainda que a taxa de sobrepeso encontrada nesta pesquisa foi superior às encontradas em outros estudos realizados com crianças assistidas por creches públicas no Nordeste do Brasil 33,34 , bem como de estudos cujo cenário não foi especificamente o contexto escolar 30,35 . Porém prevalências concordantes ou maiores que as do presente estudo foram reportadas entre crianças nordestinas, tanto as assistidas em creches 32,36 quanto as de base populacional 31,37 .…”
Section: ▄ Discussãounclassified